Changes in health among 45–64-year-old Dutch persons before, during and after becoming unemployed or employed: a seven year follow-up study - David van de Ven; Suzan JW Robroek; Karen M Oude Hengel; Alex Burdorf; Merel Schuring (Scandinavian Journal of Work, Environment & Health, 2022)

(untitled)
OBJECTIVES: This study aimed to evaluate the extent to which physical and mental health and body mass index (BMI) changed before, during and after becoming unemployed or employed, and whether these associations differ across psychosocial and physical working conditions. METHODS: Participants from seven waves (2010–2017) of the Dutch longitudinal Study on Transitions in Employment, Ability, and Motivation (STREAM) aged 45–64 years were included. STREAM provides information on physical and mental health, BMI and working conditions, and was enriched with monthly information on income components from Statistics Netherlands to define employment status during 2010–2017. Annual changes in physical and mental health (0–100 scales), and BMI (kg/m^2) before, during and after becoming unemployed (N=13 279) and employed (N=1902) were estimated with generalized linear mixed-effect models. RESULTS: Before employed persons became unemployed they had poorer health than continuously employed persons, which worsened in the period before becoming unemployed. During the year of becoming unemployed, physical [b=1.45, 95% confidence interval (CI) 0.89–2.01] and mental health (b=1.46, 95% CI 0.85–2.07) improved, in particular among persons with unfavorable working conditions. After becoming unemployed physical health deteriorated (b=-0.52, 95% CI -0.80– -0.24) and BMI (b=0.11, 95% CI 0.03–0.19) increased, but mental health improved (b=0.33, 95% CI 0.02–0.63). Unemployed persons had better health before entering employment than continuously unemployed persons. The health of persons who entered employment did not statistically significantly change before or during the year of the transition. After entering employment, physical health deteriorated and BMI increased. CONCLUSIONS: Maintaining a healthy workforce and limiting unfavorable working conditions may contribute to the prevention of unemployment and the promotion of re-integration.